2015
DOI: 10.1111/jdv.13023
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine plasma levels in psoriasis patients: our experience and review of the literature

Abstract: Our results confirm that psoriasis patients with more severe disease, can have hyperhomocysteinaemia, without regard to disease duration or joint involvement. Hyperhomocysteinaemia is not influenced by a target therapy for psoriasis and it is as greater as psoriasis severity. However, limitation of our study is the relatively small number of cases. Homocysteine plasmatic levels should be advisable as a further independent risk factor for cardiovascular disease in psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 34 publications
3
39
4
1
Order By: Relevance
“…However, unlike these results, patients with psoriasis were found to have high blood homocysteine in other five studies again in our country and five in Italy and one each in Ireland and Norway [20][21][22][23][24][25][26][27][28][29][30][31] . In the literature, studies showing psoriasis being accompanied by high blood homocysteine seem to be predominant (Table 3).…”
contrasting
confidence: 42%
See 2 more Smart Citations
“…However, unlike these results, patients with psoriasis were found to have high blood homocysteine in other five studies again in our country and five in Italy and one each in Ireland and Norway [20][21][22][23][24][25][26][27][28][29][30][31] . In the literature, studies showing psoriasis being accompanied by high blood homocysteine seem to be predominant (Table 3).…”
contrasting
confidence: 42%
“…After the studies made in 1990s where high levels of homocysteine were found in plasma samples of subjects who had or would likely to have a history of myocardial infarction, ischemic stroke or peripheral vascular disease and the association of homocysteine with atherosclerosis and hypercoagulability had been shown [6][7][8][9][10][11][12] , along with increased attention to the comorbidities of psoriasis, as far as we know, 19 studies have been conducted to explore homocysteine levels in these patients. Homocysteine level was found to be high in 12 and normal in 7 of these studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Since this sulfur-containing amino acid is not taken through diet and not producing protein, homocysteine is formed via methionine catabolism 8,11,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the study by Giannoni et al , patients with increased homocysteine levels also had decreased vitamin B 12 and folate levels. These parameters (increased homocysteine and decreased vitamin B 12 and folate) might be caused by the same determinant, which might be increased keratinocyte metabolic turnover rate in psoriasis patients [20]. On the other hand, in our study, increased homocysteine levels did not correlate with disease duration or severity, and these patients had normal vitamin B 12 and folate values.…”
Section: Discussioncontrasting
confidence: 51%
“…Thus, some reports have concluded that high homocysteine levels in patients with psoriasis are positively correlated with PASI scores, even in patients who do not have accompanying hyperhomocysteinemia risk factors. Homocysteine levels may be an independent risk factor for cardiovascular disease [19, 20]. However, in the study by Giannoni et al , patients with increased homocysteine levels also had decreased vitamin B 12 and folate levels.…”
Section: Discussionmentioning
confidence: 99%